PECULIARITIES OF THE PROJECTILE PENETRATION DEPTH WHEN FIRED WITH “FORT 9R” AND “FORT 17R” PISTOLS WHILE USING DIFFERENT CLOTHING FABRIC - Perebetiuk, A.M.; Gunas, V.I.; Fomina, L.V.; Zverkhovska, V.F.; Prokopenko, S.V. (World of Medicine and Biology, 2022)
The study of the protective qualities of various types of clothing when fired from non-lethal firearms, which are mainly used by law enforcement agencies, is one of the promising directions of the so-called humanitarian direction of forensic medicine. The conducted experimental research with the use of human body simulators covered with different types of fabric and “Fort 9R” and “Fort 17R” pistols made it possible to establish that at close-range shot distances of 50 cm and any type of fabric, a wound channel is formed to a depth of at least 1 cm; at the same time, “Fort 9R” in any case does not cause the formation of a wound channel longer than 6 cm, and “Fort 17R” deeper than 5 cm; cotton fabric has better protective qualities when fired with “Fort 9R”, and leatherette when fired with “Fort 17R”.